Drug like HSP27 cross linkers with chromenone structure ameliorates pulmonary fibrosis - Yoo, Young Jo; Jeon, Seulgi; Jin, Hee; Won, Hee Yeon; Jeong, Mi Gyeong; Cho, Yeseul; Hwang, Eun Sook; Na, Younghwa; Cho, Jaeho; Lee, Yun-Sil (Frontiers in Pharmacology, 2023)
Pulmonary fibrosis (PF) is an end-stage lung disease characterized by extracellular matrix (ECM) abnormalities, epithelial to mesenchymal transition (EMT), and differentiation of myofibroblasts derived from various cell types. This eventually leads to stiffening of the lung, which can assume only limited gas exchange function. So far, two drugs, pirfenidone, and nintedanib, have been approved for patients with idiopathic pulmonary fibrosis (IPF). Unfortunately, such drugs simply delay the occurrence of fibrosis and hence do not constitute a treatment for this illness. Heat shock protein 27 (HSP27) has previously been shown to be highly increased during radiation (IR) and bleomycin (BLM)-induced PF, and also in PF patients. Moreover, J2, a synthetic small molecule inhibitor of HSP27, significantly inhibited PF development in IR and BLM-induced PF models. Here, we developed a more druggable HSP27 inhibitor, NA49. NA49 showed an altered dimerization effect of HSP27, and inhibited PF development in both the BLM and IR mouse models. NA49 also inhibited IR-or TGF-mediated NFκB activation and EMT-related molecules such as IL-1β, IL-6, and Twist. However, NA49 showed less DNA strand break damage than J2 in human lung epithelial cells when detected by γ-H2AX and comet tail formation. From the data, applying the druggable small molecule HSP27 inhibitor without toxicity like NA49 may be a good strategy for inhibiting PF.